To what extent are faculty ready to participate in the OER movement? : The case of the Informatics School, UNA - Coto Chotto, Mayela (2017)
The success and sustainability of the Open Educational Resources (OER) movement depends to a large extent on large-scale participation in the use and production of educational resources. The aim of this paper was to explore faculty staff knowledge and behaviors about OER with a focus on resource sharing attitudes. The study was conducted at the School of Informatics of the National University of Costa Rica. Faculty were invited to respond to a questionnaire. The respondents indicated being open to the idea of sharing their own content and, as in other studies, demonstrated existing practices of sharing resources among their colleagues at the local level. However, there is little knowledge about OER and CC licenses, as well as concern about intellectual property rights, factors that hinder their participation in the movement.